Glycoprotein B Antibodies Completely Neutralize EBV Infection of B Cells - Hong, Junping; Wei, Dongmei; Zhong, Ling; Wu, Qian; Chen, Kaiyun; Zhang, Wanlin; Yang, Yanbo; Chen, Junyu; Xia, Ningshao; Zhang, Xiao; Chen, Yixin (Frontiers in Immunology, 2022)
Epstein-Barr virus (EBV) is the first reported oncogenic herpesvirus which establishes persistent infection in B lymphocytes in 95% of adults worldwide. Glycoprotein B (gB) plays a predominant role in fusion of viral envelope with host cell membrane. Hence, it is of great significance to isolate gB-specific fusion-inhibiting neutralizing antibodies (NAb). AMMO5 is the only anti-gB NAb but fails to antagonize B cell infection. It is essential to isolate potent NAbs that can completely block EBV infection of B cells. Using hybridoma technology and neutralization assay, we isolate two anti-gB NAbs 8A9 and 8C12 that are capable of completely neutralizing B cell infection in vitro. In addition, 8A9 shows cross-reactivity with rhesus lymphocryptovirus (rhLCV) gB. Competitive binding experiments demonstrate that 8A9 and 8C12 recognize novel epitopes which are different from AMMO5 epitope. The epitopes of 8A9 and 8C12 are mapped to gB D-II, and AMMO5 epitope is located precisely at gB aa 410-419. We find that 8A9 and 8C12 significantly inhibit gB-derived membrane fusion using a virus-free fusion assay. In summary, this study identifies two gB-specific NAbs that potently block EBV infection of B cells. Our work highlights the importance of gB D-II as a predominant neutralizing epitope, and aids in rational design of therapeutics or vaccines based on gB.